QFL AND LITHO FACIES: PREDICTING RESERVOIR QUALITY OF THE MIDDLE MIOCENE DEEP-WATER FACIES AT KUTEI AND NORTH MAKASSAR BASINS - Kuntadi Nugrahanto Nugrahanto; Ildem Syafri; Budi Muljana (Marine Geological Institute of Indonesia, 2021)
As we may all be aware the oil and gas wellbores offshore Kutei and North Makassar have not optimally penetrated the objective strata, which is the Middle Miocene’s deep-water reservoirs. Therefore, evaluating the quality of these reservoirs with onshore dataset then comparing them with the proven Late Miocene’s deep-water producing reservoirs had been very fundamental. The study focuses on the assessment of QFL and sandstones litho-facies based on the rock samples from conventional-core and side-wall core, and well-logs data from forty wells onshore and offshore. These rock samples are bounded by the key biostratigraphy intervals of M40M33, M45M40, M50M45 (Middle Miocene), and M65M50, M66M65, M70M66, M80M70 (Late Miocene). Subdivisions of the reservoirs considered the sandstone litho facies, NTG ratio, sorting, and grain size, to come up with five groups in the Middle Miocene deltaic facies: FLU_SX, DC_SX, DC_SM, DC_SM, and DF_SC; and four groups in the Late Miocene deep-water facies: SSWS, MSWS, SSPS, and MSPS. Core-based porosity and permeability further explain the relationship between the reservoir quality with the sandstones’ composition and litho facies, and concluded that high-energy depositional system is mainly associated with the FLU_SX, DC_SX, SSWS and MSWS being the reservoir with best quality. Oppositely, the DF_SC, SSPS, and MSPS are classified the reservoir with worst to none quality. A cross plot between core-based porosity and maximum burial depth is able to postulate the relational trend of decreasing reservoir quality with deeper depth.